National Protection Mechanisms of Human Rights Defenders in Malawi - Budoo-Scholtz, Ashwanee (University of Pretoria, 2021)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2021.